Influence of a chatbot based on a conversational agent on the adaptability of first-year students of a Peruvian private university - Yahaira Zileri Odalis Arapa Mejia; Christopher Andrew Dobson Navarro; Nancy Esther Casildo-Bedón; Yngue Elizabeth Ramirez Pezo (Frontiers in Education)
ObjectiveThis study aims to evaluate the influence of using a chatbot-based conversational agent, named ODAbot, on the adaptability of first-year students at a private university in Peru.MethodsThe design of this study was pre-experimental with a quantitative approach. The sample consisted of 53 university students who participated in the research during March and April 2024. Participants completed pre-test and post-test questionnaires to assess their adaptability to university life before and after interacting with ODAbot. Additionally, a user experience questionnaire was used to measure satisfaction with the chatbot interaction. Data were analyzed using the Wilcoxon test to determine the statistical significance of the results.ResultsThe results showed that the use of ODAbot had a significant impact on students’ adaptability, especially in the social dimension (p = 0.000), while no significant differences were found in the institutional dimension (p = 0.124). The user experience was positive, with students reporting ease of navigation and understanding of the responses provided by the chatbot.ConclusionA notable improvement was recorded in the social dimension, promoting peer integration, as well as in the academic dimension, where students expressed greater satisfaction with the information provided. However, no significant differences were observed in the institutional dimension. Overall, the implementation of chatbots presents a promising opportunity to improve the adaptability of university students and ensure a quality educational experience.